Effects of HLA-DRB1 alleles on susceptibility and clinical manifestations in Japanese patients with adult onset Still’s disease - Tomoyuki Asano; Hiroshi Furukawa; Shuzo Sato; Makiko Yashiro; Hiroko Kobayashi; Hiroshi Watanabe; Eiji Suzuki; Tomoyuki Ito; Yoshifumi Ubara; Daisuke Kobayashi; Nozomi Iwanaga; Yasumori Izumi; et al. (Arthritis Research & Therapy, 2017)
Abstract Background HLA-DRB1 alleles are major determinants of genetic predisposition to rheumatic diseases. We assessed whether DRB1 alleles are associated with susceptibility to particular clinical features of adult onset Still’s disease (AOSD) in a Japanese population by determining the DRB1 allele distributions. Methods DRB1 genotyping of 96 patients with AOSD and 1,026 healthy controls was performed. Genomic DNA samples from the AOSD patients were also genotyped for MEFV exons 1, 2, 3, and 10 by direct sequencing. Results In Japanese patients with AOSD, we observed a predisposing association of DRB1*15:01 (p = 8.60 × 10−6, corrected p (Pc) = 0.0002, odds ratio (OR) = 3.04, 95% confidence interval (95% CI) = 1.91–4.84) and DR5 serological group (p = 0.0006, OR = 2.39, 95% CI = 1.49–3.83) and a protective association of DRB1*09:01 (p = 0.0004, Pc = 0.0110, OR = 0.34, 95% CI = 0.18–0.66) with AOSD, and amino acid residues 86 and 98 of the DRβ chain were protectively associated with AOSD. MEFV variants were identified in 49 patients with AOSD (56.3%). The predisposing effect of DR5 was confirmed only in patients with AOSD who had MEFV variants and not in those without MEFV variants. Additionally, DR5 in patients with AOSD are associated with macrophage activation syndrome (MAS) and steroid pulse therapy. Conclusion The DRB1*15:01 and DR5 are both associated with AOSD susceptibility in Japanese subjects. A protective association between the DRB1*09:01 allele and AOSD was also observed in these patients. Our data also highlight the effects of DRB1 alleles in susceptibility to AOSD.